Faktor- Faktor Yang Mempengaruhi Cash Holding - Fauzie, Fany Resti; Wijayanti, Anita; Siddi, Purnama (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2020)
Increasing business competition pushes company to optimize financial management properly, especially on cash. Efforts should be made to manage cash by knowing the factors that affect the cash that must be owned by the company so that the use of cash can be utilized optimally. This study aims to determine the effect of Cash Flow, Capital Expenditure, Net Working Capital and Leverage on Cash Holding in Food and Beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2018. The sampling technique using purposive sampling, so as to obtain a sample of 44. Data analysis technique used in this study is multiple linear regression using SPSS version 22. Based on the results of data analysis conducted shows that there is an influence of Cash Flow, Net Working Capital, Leverage Cash Holdings, while Capital Expenditure does not affect Cash Holdings. The benefits of this research are as a consideration for management in making decisions related to the factors that influence Cash Holding, as well as a consideration for investors if they want to invest in a company Keywordsi: Cash Holding, Cash Flow, Capital Expenditure, Leverage, Net Working Capital